PSVII-16 Utilization of a progesterone-based protocol prior to the breeding season failed to induce puberty in Bos indicus heifers. - Canal, L (J Anim Sci, 2018)
The objective of this study was to determine the effectiveness of utilizing a progesterone-based strategy to induce puberty in Bos indicus heifers. Three hundred and eighty Bos indicus (Nelore)beef heifers were enrolled in a completely randomized design from May to June of 2017. Heifers were randomly assigned to 1 of 3 treatments: 1) Induction (IND; n=124); heifers received a CIDR insert on d 0 for 12 d and 25 mg of PGF2α at CIDR removal, and were exposed to the 5-d CO-Synch+CIDR protocol on d 24; 2) SYNCH (n=123); same as IND; however, heifers did not receive a CIDR or PGF2α between d 0 and d 12; and 3) CTRL (n=133); heifers received no treatment. On d 29 heat detection patches were applied to all heifers to detect expression of estrus between d 29 and 34. Blood samples were collected on d -10, 0 and 29 to determine heifer cyclicity, based on plasma concentrations of progesterone. Treatment groups differed (P = 0.037) in cyclicity prior to treatment initiation, where IND heifers had a greater percentage of heifers cycling compared to the SYNCH and CTRL groups (46.0 vs. 32.5 and 32.3%, respectively). On d 24, no differences (P = 0.484) were detected in cyclicity among treatments. In addition, when only prepubertal heifers were included in the analysis, no difference was detected between treatments (P = 0.617). Expression of estrus did not differ (P = 0.167) among treatments between d 29 and 34. A treatment × day interaction (P = 0.019) was detected on BW where SYNCH and CTRL heifers had greater BW than IND heifers on d 12, 24 and 29. In conclusion, the exposure of heifers to a puberty induction protocol prior to the initiation of the 5-d CO-Synch+CIDR protocol failed to induce puberty in Bos indicus beef heifers.